Dogsred. 01 - Noda, Satoru (Viz signature., 2025)
"Rou once chased figure-skating glory. Now he chases redemption in the ice hockey rink. After winning the national championship, 15-year-old figure skater Rou Shirakawa was on his way to the Olympics. But with his mother's tragic death on his mind, he threw it all away in an outburst of rage. Banned from figure skating, he and his sister move to Hokkaido. When he meets some local kids at the skating pond, they convince him to be a stand-in player for their soon-to-be-disbanded hockey team. The team has never won a game, and they're up against the local champs-but if they've got to go down, they want to score at least one goal before it's all over. Rou hasn't got a clue how to play ice hockey, but he sure knows how to skate!"--